2017
DOI: 10.1017/ssh.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

The Birth of Representative Institutions: The Case of the Crown of Aragon

Abstract: A new research agenda within political science and economics has been devoted to elucidating the development of medieval representative institutions. However, if we wish to get a clearer grasp of the birth of representative institutions, much more detailed data are needed. This paper introduces and interrogates a new data set on assemblies in one of the first instances where representative institutions arose: the Crown of Aragon. An analysis of these new data, which cover the period 1100–1327, supports several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…Recent research has shown that the establishment of representative assemblies may indeed have enabled monarchs to better shoulder the costs of war. Scholars have highlighted increased warfare among parliamentary "first movers," such as twelfth-century Aragon (Møller, 2016) and thirteenth-century England (Boucoyannis, 2015). Similarly, Stasavage (2016, p. 155) finds a significant statistical relationship between warfare and parliamentary activity across pre-modern Europe.…”
Section: "Parliamentary Governments Caused War"mentioning
confidence: 99%
“…Recent research has shown that the establishment of representative assemblies may indeed have enabled monarchs to better shoulder the costs of war. Scholars have highlighted increased warfare among parliamentary "first movers," such as twelfth-century Aragon (Møller, 2016) and thirteenth-century England (Boucoyannis, 2015). Similarly, Stasavage (2016, p. 155) finds a significant statistical relationship between warfare and parliamentary activity across pre-modern Europe.…”
Section: "Parliamentary Governments Caused War"mentioning
confidence: 99%
“…Hence, by working backwards from large-scale developments we often miss surprising initial aspects of a given development, which are not on the radar of the social scientist with a preconceived explanation to test. The example that I use as a foil throughout the paperthe study of the origins of medieval representative institutionsis a good example of this (Møller 2016; but see Boucoyannis 2015). However, the fine-grained data used in the congruence analysis and the ability to interpret it in a qualitative way makes it much easier to identify surprising developments, which occurred relatively fast, in a forward-looking way.…”
Section: Guidelines For Congruence Analysismentioning
confidence: 99%
“…Furthermore, this information also stipulates the groups partaking in assemblies, the reasons for convoking them, and the decisions arrived at. In this paper, I use the case of the Crown of Aragon to illustrate the congruence method but elsewhere I have analyzed the English development in a similar way (Møller 2016).…”
Section: Case Selectionmentioning
confidence: 99%
See 2 more Smart Citations